Reporting Rape: Stigmatizing Reactions to Survivors Who Seek Accountability - Maryn, Alyssa Glace (Violence against women, 2024)
Rape survivors face stigma when disclosing their experiences. We hypothesized that a rape survivor who formally reports their rape would experience more stigma than one who does not, and that this effect will be stronger when the perceiver is a man or low in support for sexual consent. Across two studies using self-report, observational, and psychophysiological measures, we found that a reporting survivor was seen more negatively than an identical survivor who did not report their rape. Men and those low in support for sexual consent also responded more negatively to the survivor. Implications of these findings are discussed.